Sistem Pakar Diagnosa Penyakit Pyelonephritis Pada Manusia Dengan Menggunakan Metode Fuzzy Mamdani - Hotmaria Sianturi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Observing everyday life in society seems to be not only an educational, economic, and cultural factor which is a big problem for people today. It turns out that social factors related to the level of well-being, and public health are far more important issues to pay attention to. Because as we all know that the level of living welfare greatly impacts on the health level of the community itself. The choice of the problem concerning the type of Pyelonephritis in the human kidney as a sample of this study, is the fact that the kidney is an important organ in our body's metabolic system, because of the density of activities, we often forget to look after it. Irregular eating patterns, lack of fiber intake and mineral water, and consumption of high-calorie instant foods or drinks, have unwittingly made the kidneys work harder. In general, many people are reluctant or reluctant to see a doctor when they feel the symptoms experienced or also influenced by the absence of fees for consulting a doctor or the limitations of doctors in a particular area, causing handling of patient consultations less effectively and efficiently. So by relying on advancements in technology and information, it is very important to apply expert systems to diagnose diseases in the kidneys. This expert system was created for processing consultation data on pyelonephritis in the kidneys which can be done digitally, so that time is more effective, efficient and helps to deal with patients who are faster consulted. To produce a more accurate expert system, a supporting method is needed, namely fuzzy mamdani method